Corporate Governance's Impact on Sustainable Finance: An Analysis of Borsa Istanbul Energy Sector Companies - Zehir, Cemal; Ozyesil, Mustafa; Borodin, Alex; Akturk, Esin Benhur; Faedfar, Sara; Cikrikci, Mustafa (MDPI, 2023)
The main purpose of this study is to conduct an evaluation based on listed companies traded in the energy sector sub-market of Borsa Istanbul (BIST). This evaluation is conducted on a sample of 27 companies between 2016 and 2021. In this study, corporate governance indicators are used as independent variables, while financial performance indicators are used as dependent variables. Initially, descriptive statistics of the sample and correlations between variables were calculated and interpreted in the analysis, and the Panel Data Analysis method is applied for the interaction between variables. This study emphasizes the importance of global economic and social crises, rapid changes in communication technologies, and the concept of sustainability for businesses. The sustainability of financing is highlighted as vital for companies. The findings of the study may serve as a valuable resource for understanding the performance of companies operating in the energy sector sub-market of BIST and their relationships with sustainability.
Keywords: engineering; corporate governance; sustainability; CMB; financial performance; Borsa Istanbul exchange energy companies; PERFORMANCE; FIRM; Energy & Fuels